أثر المهارات القيادية في أداء العاملين في المؤسسات العامة بمحافظة البيضاء - اليمن - الجرادى، أحمد محسن ثابت; الأشول، محمد عبدالله أحمد; الأقرع، سعد عبدالله أحمد قاسم (جامعة البيضاء, 2020)
تهدف الدراسة إلى التعرف على أثر المهارات القيادية في أداء العاملين في المؤسسات العامة بمحافظة البيضاء -اليمن. استخدم المنهج الوصفي التحليلي في إجراء هذه الدراسة من خلال جمع البيانات من مصادرها الأولية والثانوية، كما تم تصميم استبيان كأداة لجمع البيانات واستخدام الباحثون أبعاد المهارات (الذاتية، والفنية والإدارية، والإنسانية، والفكرية) للقيادات في المؤسسات العامة في محافظة البيضاء ومستوى أداء العاملين وذلك من خلال وجهة نظر العاملين. وبعد تحليل البيانات باستخدام برنامج التحليل الإحصائي (SPSS). توصلت الدراسة إلى مجموعة من النتائج أهمها، تكشف نتائج تحليل الانحدار البسيط أن هناك أثر طرديا ذا دلالة إحصائية لكل بعد من أبعاد المهارات القيادية ومستوى أداء العاملين. في حين أظهرت نتائج تحليل الانحدار الخطي المتعدد أن المهارات الإنسانية فسرت ما مقدار (41%) من التباين في مستوى أداء العاملين، في حين خرجت باقي أبعاد المهارات القيادية من معادلة الانحدار الخطي المتعدد، حيث لم يكن هناك أي دلالة إحصائية وبالتالي لم تستطع تفسير التباين في مستوى أداء العاملين بالرغم من وجود الأثر المعنوي لتلك الأبعاد على مستوى أداء العاملين عند دراستها بشكل منفرد The study aims to identify the impact of leadership skills on the performance of employees in public institutions in Al Bayda Governorate Yemen. The descriptive analytical approach was used in conducting this study by collecting data from its primary and secondary sources, and a questionnaire was designed as a tool to collect the data and the researcher uses the dimensions of skills (Self-skills - Technical and Administrative skills - Intellectual skills - Human skills) of the leaders working in the institutions in Al Bayda Governorate and the level of employee performance, from the point of view of employees. After analyzing the data using the statistical analysis program (SPSS). The study reached a set of results, the most important of which are, The results of the simple regression analysis reveal that there is a statistically significant effect of each dimension of leadership skills and the level of employee performance. While the results of the multiple linear regression analysis showed that human skills explained (41%) of the variance in the level of employee performance, while other dimensions of leadership skills come out of the linear regression equation, where there was no statistical significance and therefore could not explain the variation in the level of employee performance Although there is a significant effect of these dimensions on the employee's performance when studying it individually.
Keywords: المؤسسات العامة -- المهارات القيادية -- أداء العاملين -- محافظة البيضاء -- اليمن